Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Toko Swalayan Multi Mart Cabang Gisting Atas Kabupaten Tanggamus - Vivi Tri Wulandari; Vicky F Sanjaya; Santi Hermalia . (Universitas Mitra Indonesia, 2021)
This study aims to determine what the effect of the work environment on employee performance. In this study using a quantitative research method (questionnaire) with 35 informants collected from multi mart gisting atas kec. Gisting kab. Tanggamus with data analysis techniques using PLS. The result obtained from this study are work environment variables that have a significant influence on employee performance.